"Pulling the sheep's wool": The labour of online thrift in a Chinese factory. (May 2022) - McDonald, Tom; Dan, Li
This paper draws on data collected during ethnographic fieldwork in a factory in south-east China to describe the significance of a group of activities colloquially known as "pulling the sheep's wool" ( haoyangmao ). This wide-ranging set of thrift-oriented practices involves gaining rewards and discounts by collecting various credits and points, most often through activities conducted on online shopping, news and payment platforms. Recent studies have sought to reposition thrift as a morally-infused consumptive practice for the creation of value, through which the concept of the house is enacted. However, this paper demonstrates how thrift is viewed by labourers as a kind of "work". As such, it is able to act in a factory environment largely unmoored from notions of domesticity, instead delineating social boundaries between production line workers and managers, fostering communal behaviours amongst labourers and—through a process of earmarking—allowing for workers to direct a greater share of their wages toward household economies. We argue that this conception of thrift as labour actually reworks the way that consumption conjoins with production, challenging our received understandings of consumption, while also providing new possibilities for the creation of both value and personhood.